Comparative Analysis of Digital Technology in Architectural, Engineering Construction Industries Across Six Continents of the World: A Global Perspective - Fakoyede, Peter Dayo; Diouf, Mame Diarra Bousso; Aruya, Grace Agbons; Fakoya, Isaac Ajibola; Enabulele, Ewemade Cornelius; Adeleke, Olaniyi Benjamin; Daramola, Merinubi Sunday; Adeyemi, Taiwo Oluwaseun (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2024)
This paper investigates integrating and comparing digital technology in the architectural, engineering, and construction (AEC) industry on the world's six continents, concentrating on the adoption of designs, points of interest, and suggestions for AEC instruction. The study draws insights from current research and industry reports to underline the five most recent popular digital technologies—building Information Modeling (BIM), 3D Printing, the Internet of Things (IoT), Digital twins, and GIS—and their significance and the importance of aligning construction education with industry innovations. The subject utilizes an online survey, exhaustive online information search (using search engines), and choices of journals for the investigation. To begin with, the five biggest economies nations of each continent, but Antarctica was partially utilized for comparison in this subjective research to complete the seven continents of the world. The result appears that North America (US and Canada) and Europe (UK, France, and Germany) are the driving pioneers and early adopters of digital technology in architecture, engineering, and construction. Asia (China, Seoul) The AEC market is adopting this digital technology spontaneously. Oceania (except Australia) is behind Asia in the adoption rate; South America and Africa are the late adopters of this digital technology in the industry.